Program Studi Pendidikan Guru Sekolah Dasar, Universitas Sarjanawiyata Tamansiswa - Shanta Rezkita; Ana Fitrotun Nisa (Universitas Sarjanawiyata Tamansiswa, 2016)
Taman Muda IbuPawiyatanYogyakarta Vision is to be a quality school, arts-based cultural and educational noble character. Therefore, any learning activity seeks to implement the values of character and concepts ketamansiswaan, including on science learning (IPA). Translating that vision relevant to the purposes of science education that not only emphasizes the development of students’ knowledge of science, but also help the development of students into well-rounded individual with good character. This study aims to explore the implementation of character value through the development of science process skills for students with special needs, values character of the development of science process skills and the factors that influence its implementation. This study is descriptive qualitative research. Data collection techniques include observation, interviews, and documentation. Mechanical analysis of data through data reduction, data presentation, and conclusion. Testing the credibility of both the source and use triangulation techniques, the extension of observation, and check data providers (member check). Implementation of character value through the development of science process skills for students with special needs high class Taman Muda IP Yogyakarta had walked though not maximized, both in terms of planning, implementation, and assessment. The values of character can be extracted including gender, honest, independent, responsibility, willpower, and appreciate nature. Its success is influenced by the family environment, school, and community.